Analysis of 5S Work Culture Implementation: The Role of Leadership and Employee Engagement on Business Performance in the Manufacturing Industry - Faisal Ibrahim; Sutrisno, Wahyudhi (ARRUS Journal of Engineering and Technology, 2025)
This study examines the implementation of the 5S work culture in PT XYZ International, focusing on the roles of leadership commitment and employee involvement in enhancing business performance. The 5S principles—sorting, organizing, cleaning, standardizing, and sustaining discipline—are analyzed to identify critical factors influencing their effectiveness. Using Structural Equation Modeling-Partial Least Squares (SEM-PLS), data were collected from 100 respondents through questionnaires and analyzed to evaluate relationships between variables. The results indicate that leadership commitment and employee involvement significantly influence the implementation of the 5S work culture, accounting for 33.1% of the variation in business performance. However, suboptimal employee adherence to 5S principles remains a challenge, impacting the overall effectiveness of the work culture. Key findings highlight areas for improvement in technical and social aspects, with actionable recommendations proposed to enhance 5S implementation and business outcomes. This study contributes to understanding the integration of 5S principles in Indonesian manufacturing companies and offers insights for similar organizations aiming to optimize their operational efficiency.